Pengaruh Profesionalisme Guru, Proses Pembelajaran dan Sarana Prasarana Belajar terhadap Prestasi Belajar Peserta Didik - Dilla, Astriaa Ratu; Martono, Trisno; Wahyuni, Sri (Department of Economics Education, Universitas Sebelas Maret, 2019)
This research aims to determine (1) The influence of professionalism teachers, learning process and learning infrastructure to learning achievement of students class X on business economic subject at SMK Batik 2 Surakarta (2) The influence of professionalism teachers to learning achievement of students class X on business economic subject at SMK Batik 2 Surakarta (3) The influence of learning process to learning achievement of students class X on business economic subject at SMK Batik 2 Surakarta (4) The influence of learning infrastructure to learning achievement of students class X on business economic subject at SMK Batik 2 Surakarta. The type of the research that used by the author to achieve that goal is descriptive quantitative method by data collection techniues in the form of a questionnaire and documentation. The population of this research ere students of class X Accounting and Office Administration totaling 79 students. The analysis data technique are used statistic analyzed with multiple regression. Based on the result of the research, it can be concluded that (1) There is a positive and significant influence of professionalism teachers, learning process and learning infrastructure together to learning achievement of students. This is proven from the F test value obtained Fcalculation 74,235 > Ftable 2,73. (2) There is a positive and significant influence of professionalism teachers to learning achievement of students. This is proven from the t test vale obtained tcalculation 4,347 > ttable 1,99210. (3) There is a positive and significant influence of learning process to learning achievement of students. This is proven from the t test vale obtained tcalculation 3,146 > ttable 1,99210. (4) There is a positive and significant influence of learning infrastructure to learning achievement of students. This is proven from the t test vale obtained tcalculation 2,057 > ttable1,99210.